Determinants of patient delay in doctor consultation in head and neck cancers (Protocol DEREDIA). Issue 7 (25th July 2014) - Christophe, Véronique; Leroy, Tanguy; Seillier, Mélanie; Duthilleul, Camille; Julieron, Morbize; Clisant, Stéphanie; Foncel, Jérôme; Vallet, Fanny; Lefebvre, Jean-Louis
Abstract : Introduction: Reducing the time between the onset of the first symptoms of cancer and the first consultation with a doctor (patient delay) is essential to improve the vital prognosis and quality of life of patients. Longer patient delay is linked to the already known sociodemographic, socioeconomic, socioeducational, sociocultural and socioprofessional factors. However, recent data suggest that some sociocognitive and emotional determinants may explain patient delay from a complementary point of view. The main objective of this study is to assess whether, in head and neck cancer, patient delay is linked to these sociocognitive and emotional factors, in addition to previously known factors. Methods and analysis: We intend to include in this study 400 patients with a not yet treated head and neck cancer diagnosed in one of six health centres in the North of France region. The main evaluation criterion is 'patient delay'. Sociocognitive, emotional, medical, sociodemographic, socioeconomic, educational, professional and geographic factors will be assessed by means of (1) a case report form, (2) a questionnaire completed by the clinical research associate together with the patient, (3) a questionnaire completed by the patient and (4) a recorded semidirective interview of the patient by a psychologist (for 80 patients only). The collected data will be analysed to underline the differences between patients who consulted a doctor earlier versus those who consulted later. Ethics: The study has obtained all the relevant authorisations for the protection of patients enrolled in clinical trials (CCTIRS, CCP, CNIL), does not involve products mentioned in article L.5311-1 of the French Code of Public Health, and does not imply any changes in the medical care received by the patients. The study began in October 2012 and will end in June 2015. Trial registration: ID-RCB 2012-A00005-38.